Retrospective investigation of IgM antibodies against Zika virus in serum from febrile patients in Mozambique, 2009–2015 - Chelene, Imelda Rogério (BMC Res Notes, 2019)
OBJECTIVE: Zika virus (ZIKV) has emerged as an important health problem worldwide. The aim of this study was to investigate the occurrence, geographical distribution and trend of immunoglobulin M (IgM) antibodies against ZIKV between 2009 and 2015 in Mozambique. RESULTS: The median age of participants was 3 years [interquartile range (IQR): 1.0–6.0 years)] and 56.5% (480/850) of them were male. Of the 850 samples, 42 (4.9%) were positive for IgM antibodies against ZIKV. Positive samples were found in 9 provinces of the country. Frequency of IgM antibodies against ZIKV was slightly higher in patients aged 5–9 years old, and in the north region of the country.